The Principle of Proportional Contracting in Sharia Bank Financing Contracts in Optical Maqasid Sharia - Kurrohman, Taufik (JURNAL AKTA, 2025)
The principle of proportionality in Sharia financing contracts upholds equality. The manifestation of equality cannot be seen mathematically but is oriented towards legal equality. The same proportion in the contractual relationship between the parties is manifested in the clauses of the agreement contract. Contractual justice can be realized with two approaches to value: the first is a technical approach that focuses on freedom of will in a contract, and the second is a substantial approach that is reflected in the clauses of the contract. Both approaches will reflect the contract proportionally and distort the dominance of freedom of contract. The method of binding sharia banks which is relatively the same as conventional banks, is one of the factors that builds the perspective of the community that sharia banks are the same as conventional banks but ignores the differentiating meaning of sharia banks is the content of the contract clauses based on sharia principles, especially fiqh muamalat. The research method was conducted descriptively and analytically with a normative legal approach. The results of the study show that first, the principle of proportional contracting based on maqasid sharia can be realized with a balance of risk and benefit (al qurmu bilgurmi), educating individuals is realized with professionalism, transparency, and honesty (dar'ul mafasid aula min jalbil manafi), and the realization of actualized benefits through supervision of sharia contract products based on sharia compliance. Second, the application of the principle of proportionality in contracting in sharia financing contracts is not by maqasid sharia, this is reflected in the major premise of the clause of the sharia bank financing contract such as the mechanism for paying obligations, tax deductions, providing collateral guarantees, breach of promise and clauses of negligence of guarantee statements and clauses of accelerated repayment deductions.